«Energy Regulatory Commission»: Character and functions after energy reform - Salerno, Paolo (2016)
The Mexican energy reform in December 2013 has represented a radical change in the structure of the sector, which has grown from a public monopoly to a competitive market. This article aims to analyze the attributions and the legal and administrative nature which has be granted to the Energy Regulatory Commission (CRE) after the normative change that will play a key role in the correct implementation thereof. The nodal problem is to confirm if the CRE has being given the correct legal instruments to develop its function autonomously and transparently.